Typical Dynamics of Volume-Preserving Homeomorphisms. - Alpern, Steve, 1948- (Cambridge tracts in mathematics., 2001)
This book provides a self-contained introduction to typical properties of volume preserving homeomorphisms. Stress is given to the interrelation between typical properties of volume preserving homeomorphisms and typical properties of volume preserving bijections of the underlying measure space. An excellent introduction for newcomers, and an indispensable resource for experts.